Numerical Study and Multi Objective Optimization of Coffee Husk Oil and Methyl Alcohol in Mini Channel Pin Fins with Varying Thickness - S. Das; N. Gnanasekaran (Journal of Applied Fluid Mechanics)
The purpose of this paper is to study how coffee husk oil and methyl alcohol flow and transfer heat in mini channel pin fins of different thicknesses. TOPSIS method is used to find the best configuration based on different weightages assigned for the Nusselt number and pumping power for multiple objectives. The present research work also determines the most effective configuration of mini-channel with varying pin-fin thickness in order to improve the thermo-hydraulic characteristics in compact mini-channels. Coffee husk oil and methyl alcohol are used as feedstock in a continuous flow mini-channel reactor to produce biodiesel fuel. Numerical simulations are conducted to evaluate the pressure drop, Nusselt number, temperature distribution, and pumping power for varying Reynolds number. Considering the conjugate heat transfer problem, the parameters involved are the enhancement factor, friction factor, and thermo-hydraulic performance parameter. The Reynolds number ranges from 100 to 600 for coffee husk oil and 100 to 660 for methyl alcohol. TOPSIS is applied to each case based on the numerical simulations to determine the optimal results. Upon evaluating the performance score using TOPSIS for all the scenarios, it is evident that the mini-channel with a pin thickness of 2.3 mm outperforms other mini-channel pin fin designs in most cases, for both coffee husk oil and methyl alcohol.